แนวความคิดทางกฎหมายมหาชนในประเทศไทย ว่าด้วยอำนาจรัฐ ตั้งแต่ พุทธศักราช 2411 ถึง พุทธศักราช 2475 - เอกลักษณ์ ลิ้มศิริลักษณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
To demonstrate the development of the concept of modern public law regarding state power, which has dominated the Thai administration since the reign of King Chulalongkorn. Such administration led first to the regime of the absolute monarchy and then to a modern state. During the reign of King Chulalongkorn, the concepts of modern public law were widely understood by the rulers, lords, well-educated people and those interested in foreign political doctrines. King Chulalongkorn reformed the country in various aspects, particularly in politics and administration. The reforms had an effect on the public law i.e. rapid limitation of lords power in the old regime and centralization of power in the hands of the king. However, a group of people attempted to challenge the absolute monarchy regime. This group called for the change of the administration by asking for promulgating of a constitution which is the highest law and where the king is under the law. His Majesty the King did not agree. The notion of such challenge most possibly affects the idea of King Chulalongkorn such that the state power is divided into legislative power, administrative power and judicial power and the king exercises three powers through the political institutions established. In the reign of King Vajiravuth, his Majesty the King was expected to establish an administration in the form of a parliamentary regime and a written constitution immediately at the time of his ascendancy of the throne. Nevertheless, his Majesty the King did not do so. This resulted such dissatisfaction among a group of new soldiers that there was an attempt to change the regime. During the reign of King Vajiravuth, the constitution was not granted to people and the absolute monarchy still remained in place. Subsequently in the reign of King Prajadhipok, his Majesty the King tried to give a constitution to people twice. His Majesty the King assigned Francis B. Sayre first and secondly Mr. Stevens and Phya Srivisanvaja to take care of the process of establishing theconstitution. This was objected to by the elderly members of the royal family, particularly Prince Damrong Rajanubhab. The draftsmen of the constitution in the second round were of the opinion that Siam was not ready for the change. This caused his Majesty the King to hesitate and not to grant a constitution for the people. Finally, in B. E. 2475, there was a revolution and a change of the regime.